The Effect of Learning Kitab Sirah Urjuzah Mi'iyah on the Formation of Prophetic Character Traits in Santri Kuttab Al-Fatih Malang - Nur Fadilah, Tri; Tobroni; Yusuf, Muhammad (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine the learning of Sirah Urjuzah Mi'iyah and its influence on the formation of prophetic character traits in Kuttab Al-Fatih Malang students. This type of research method is an associative quantitative method. The research was conducted for the entire population of Qonuni 3 and 4 classes totaling 68 students. The data collection method used is in the form of distributing questionnaires to students. The data analysis method used by researchers is normality test, linearity test, hypothesis testing using simple linear regression test. Learning Kitab Sirah Urjuzah Mi'iyah uses two methods: first, the tashih method in which students memorize the verses of the nadzam repeatedly; second, the syarah method in which teachers interpret, interpret, and explain the meaning of the verses. In the percentage of influence between variable X and variable Y obtained from the analysis of the coefficient of determination test which shows the results of the R square value of 0.419, this shows that the learning variable of the sirah urjuzah mi'iyah book has an influence of 41.9% on the variable character building of prophetic traits in students, then as much as 58.1% is influenced by other factors.